Image Processing Categorization and Fuzzy Logic: A Survey - Nityaselvy, K.; Ramachandiran, R. (IJRDO -Journal of Computer Science Engineering, 2015)
ctImage categorization is one of the criticalperformances in sensing the crops from slightlysensed data as planning of crops is a compositeactivity which in turn is an main parameter for designand managing of irrigation facility area. categorizedremotely sensed data into a thematic map remains achallenge because many factors, such as thecomplexity of the landscape in a study area, selecteddistantly sensed data, and image-processing andorganization approaches, may affect the success of aclassification.